PERANAN AKTOR DALAM PENGELOLAAN BANK SAMPAH BERKELANJUTAN DI KOTA MEDAN (THE ROLE OF ACTORS IN MANAGING SUSTAINABLE WASTE BANKS IN MEDAN CITY) - Dumora Jenny Margaretha Siagian (Inovasi, 2019)
The problem of waste management in Medan City is quite complex so that often the efforts made by the government have not yet had a significant impact on environmental cleanliness. In essence, waste management cannot only be done by the government, but it is also very important for community involvement. Waste management should be carried out holistically by paying attention to ecological, social and cultural aspects. The waste bank as a place for sorting and collecting garbage has the aim to educate and cultivate waste reduction at the community level as well as a place for people to participate in waste management activities. In maintaining the operational sustainability of this waste bank is not an easy thing. Many challenges and problems faced by actors. This study aims to analyze how the roles of actors in maintaining the operational sustainability of waste banks in the city of Medan. The research method used a qualitative approach with ethnographic methods from Spradley. Data collection is carried out in natural settings, primary data sources, and more data collection techniques in participant observation, in-depth interviews, and documentation. The results of the study explain that the actors who play a role in the management of waste banks in Medan City include customers, waste banks (parent and unit), collectors and rodents, botots and companies (vendors). Interaction between agents and actors runs in an interest based on the dimensions of space and time, or in other words, repositioning between agents and actors is adjusted to the situation. In addition, the government also plays an important role in the sustainability of waste banks, both in administration and as a waste bank structure. Based on the results of the field, there are 3 aspects that the actors have, so they are able to survive and continue to have the will to develop a waste bank. These aspects are Strategy, Social Network by forming cooperation and networks, and Socialization of waste management. These aspects are very important for actors to fight for and develop waste banks. Keywords: role, actor, management, waste bank, Medan City